334 Relationship Between Acute Kidney Injury (AKI) using AKI Network Criteria and Brain MRI Findings in Asphyxiated Newborns after Therapeutic Hypothermia. (October 2012) - Sarkar, S; Jordan, B; Bhagat, I; Bapuraj, JR; Dechert, R; Selewski, D
Abstract : We hypothesized that hypoxic-ischemic lesion on brain MRI would differ between infants with AKI compared to those without AKI following cooling. Methods: 88 consecutively cooled infants who had brain MRI were reviewed. All infants had renal function assessed before the start of cooling (baseline); at 24, 48, and 72h through cooling; and then on day 5 or 7 of life. Injuries to both basal nuclei and cortex on MRI were considered severely abnormal. Results: AKI was found in 34 (39%) of 88 infants with 15, 7, and 12 fulfilling AKI network criteria for stage I, II, and III, respectively. Hypoxic-ischemic lesion on brain MRI was present in 50 infants. In 26 infants (AKI 14, no AKI 12), MRI was severely abnormal. Abnormal MRI was more frequent in the AKI group (AKI 25 of 34, 73% versus No AKI 25 of 54, 46%, p=0.012, OR 3.2, 95% CI 1.3–8.2). Multivariate analysis identified only the AKI (p=0.032, OR 2.9, 95% CI 1.1–7.6), and chest compression for resuscitation to be independently associated with primary outcome. Severely abnormal MRI were similar between infants with stage III and stage II AKI (stage III 3 of 12, 25% versus stage II 3 of 7, 43%; p=0.617), or stage I AKI (stage III 3 of 12, 25% versus stage I 8 of 15, 53%; p=0.238). Conclusions: AKI is independently associated with the presence of hypoxic-ischemic lesions on post-cooling brain MRI. However, the severity of AKI did not correlate with the severity of brain MRI abnormalities.